Penerapan Metode Activity Based Costing Dalam Penetapan Biaya Tarif Rawat Inap Pada Klinik Divari Medical Center - Parastri, Desirianingsih Haryati; Simanjuntak, Verawati; Dolla, Yusrianti (Fakultas Ekonomi dan Bisnis Universitas Papua, 2025)
ABSTRACT In determining inpatient tariffs, Divari Medical Center Clinic currently applies a traditional costing method that allocates costs based on room class and length of stay. As a result, the tariffs charged to patients vary according to facilities and duration of treatment. This study aimed to analyze the implementation of the existing costing methodology, determine the amount of inpatient tariffs, and examine the differences between the Activity-Based Costing (ABC) method and the traditional method in calculating inpatient service costs at Divari Medical Center Clinic, Manokwari. This study employed a quantitative descriptive approach, with data presented in numerical form, particularly inpatient room cost data. The application of the ABC method revealed that the actual costs of inpatient services were significantly higher than the tariffs currently applied by the clinic. The calculated costs per day were Rp. 1,136,345 for Class VVIP, Rp. 1,162,544 for Class VIP, Rp. 1,083,771 for Class I, and Rp. 1,081,794 for Class II. The differences between the ABC-based costs and the existing tariffs were Rp. 488,825 for VVIP rooms, Rp. 616,116 for VIP rooms, Rp. 636,061 for Class I rooms, and Rp. 732,002 for Class II rooms. These findings indicate that the traditional tariff system does not accurately reflect the actual costs incurred for each category of inpatient service at Divari Medical Center Clinic. The ABC method provides a more precise cost allocation and may serve as a more reliable basis for determining inpatient tariffs. Keywords: Divari Medical Center Clinic (DMC), Activity Based Costing Method, Traditional Method ABSTRAK Dalam penetapan tarif rawat inap, klinik ini masih menerapkan metode tradisional, yaitu menentukan biaya berdasarkan kelas kamar dan durasi perawatan, sehingga tarif yang dikenakan pada pasien bervariasi sesuai fasilitas dan lama perawatan. Tujuan dari Penelitian ini untuk menganalisa penerapan metodologi, besaran tarif rawat inap dan selisih dengan menggunakan Activity Based Costing (ABC) dan tradisional dalam perhitungannya biaya rawat inap di Klinik Divari Medical Center. Metode yang Studi ini menggunakan pendekatan deskriptif kuantitatif dan data yangdisajikan dalam bentuk numerik, seperti data biaya kamar rawat inapMelalui penerapan metodologi ABC di Klinik Divari Medical Center Manokwari, diperoleh hasil bahwa biaya aktual jauh lebih tinggi dibandingkannya dengan tarif rawat inap yang saat ini berlaku, Untuk Kelas V.VIP Rp.1.136.345, kelas VIP Rp.1.162.544, Kelas I Rp. 1.083.771, Kelas II Rp. 1.081.794, sertaSelisih tarif tersebut masing-masing sebesar Rp 488.825 untuk kamar VVIP, Rp 616.116 untuk kamar VIP, Rp 636.061 untuk kamar kelas I, dan Rp 732.002 untuk kamar kelas II. Temuan ini mengindikasikan bahwa sistem tarif tradisional belum sepenuhnya menggambarkan biaya aktual yang dikeluarkan untuk setiap jenis layanan rawat inap di Klinik Divari Medical Center. Kata kunci: Klinik Divari Medical Center (DMC), Metode Activity Based Costing, Metode Tradisional.